ChemInform Abstract: Copper‐Catalyzed Propargylic Substitution of Dichloro Substrates: Enantioselective Synthesis of Trisubstituted Allenes and Formation of Propargylic Quaternary Stereogenic Centers. Issue 19 (May 2015) - Li, Hailing; Grassi, David; Guenee, Laure; Buergi, Thomas; Alexakis, Alexandre
Abstract: An easy and versatile Cu‐catalyzed propargylic substitution process is presented.